Cross-species metabolomic analysis of tau- and DDT-related toxicity. Issue 2 (3rd May 2022) - Kalia, Vrinda; Niedzwiecki, Megan M; Bradner, Joshua M; Lau, Fion K; Anderson, Faith L; Bucher, Meghan L; Manz, Katherine E; Schlotter, Alexa Puri; Fuentes, Zoe Coates; Pennell, Kurt D; Picard, Martin; Walker, Douglas I; et al.
Abstract: Exposure to the pesticide dichlorodiphenyltrichloroethane (DDT) has been associated with increased risk of Alzheimer's disease (AD), a disease also associated with hyperphosphorylated tau (p-tau) protein aggregation. We investigated whether exposure to DDT can exacerbate tau protein toxicity in Caenorhabditiselegans using a transgenic strain that expresses human tau protein prone to aggregation by measuring changes in size, swim behavior, respiration, lifespan, learning, and metabolism. In addition, we examined the association between cerebrospinal fluid (CSF) p-tau protein—as a marker of postmortem tau burden—and global metabolism in both a human population study and in C. elegans, using the same p-tau transgenic strain. From the human population study, plasma and CSF-derived metabolic features associated with p-tau levels were related to drug, amino acid, fatty acid, and mitochondrial metabolism pathways. A total of five metabolites overlapped between plasma and C. elegans, and four between CSF and C. elegans . DDT exacerbated the inhibitory effect of p-tau protein on growth and basal respiration. In the presence of p-tau protein, DDT induced more curling and was associated with reduced levels of amino acids but increased levels of uric acid and adenosylselenohomocysteine. Our findings in C. elegans indicate that DDT exposure and p-tau aggregation both inhibit mitochondrial function and DDT exposure can exacerbate the mitochondrial inhibitory effects of p-tau aggregation. Further, biological pathways associated with exposure to DDT and p-tau protein appear to be conserved between species.